In What Circumstances Flexible Working Arrangement Possible to be Implemented?: A Literature Review - Fatmawati Aditya Febrita; Eko Prasojo (Asian Journal of Social and Humanities, 2023)
A new paradigm has emerged in the world of work amidst the widespread of the COVID-19 pandemic. One concept that has garnered attention is the "Flexible Working Arrangement." This flexible approach to work has become crucial as the pandemic has forced many companies and employees to adapt to uncertain and ever-changing circumstances. In facing these challenges, flexibility in carrying out work activities has become increasingly important. Flexible Working Arrangement provides an effective solution to overcome the obstacles arising from social restrictions and remote work. FWA has not been fully implemented by ASN, even though Presidential Decree 21 of 2023 has been issued, as a form of legal certainty for the flexible policy and the success of the WFH work system during Covid-19. By leveraging technology and digital communication, workers can remain productive without being physically present in the office. This approach enables individuals to work from home, manage a more flexible work schedule, and utilize their time more efficiently. In this paragraph, we will further discuss the benefits and implications of Flexible Working Arrangement in the context of the COVID-19 pandemic.